CRISPR-Assisted Multiplex Base Editing System in Pseudomonas putida KT2440 - Sun, Jun; Lu, Li-Bing; Liang, Tian-Xin; Yang, Li-Rong; Wu, Jian-Ping (Frontiers in Bioengineering and Biotechnology, 2020)
Pseudomonas putida KT2440 is a paradigmatic environmental-bacterium, which possesses great potential in synthetic biology, metabolic engineering and biodegradation. However, most genome editing methods in P.putida KT2440 were still depend upon heterologous repairing proteins and the provision of donor DNA templates, which was tedious and laborious. Here, we established an efficient cytosine base editing system by the fusion of cytidine deaminase (APOBEC1), enhanced specificity Cas9 nickase (eSpCas9ppD10A) and uracil DNA glycosylase inhibitor (UGI). This base editor is endowed with the capability of converting C: G into T: A in the absence of DNA strands breaks and donor DNA templates. By introducing a premature stop codon in target spacers, we had successfully applied this system for gene inactivation with an efficiency of 25%~100% in multiple Pseudomonas species, including P.putida KT2440, Pseudomonas aeruginosa PAO1，Pseudomonas fluorescens Pf-5 and Pseudomonas entomophila L48. To expand base editing candidate sites, we engineered an eSpCas9ppD10A-NG variant with a NG protospacer adjacent motif (PAM). By modifying the APOBEC1 domain, we successfully narrowed the editable window for the purpose of increasing gene inactivation efficiency in cytidine-rich spacers. In addition, multiplex base editing in double-locus and triple-locus were achieved by a two-plasmid system with the mutation efficiencies of 90% and 40%, respectively. Taken together, the establishment of a fast, convenient and universality base editing system will greatly accelerate the pace for P.putida KT2440 and other Pseudomonas species in future research.